Behavioural deviance and maternal depressive symptoms in paediatric outpatients. Issue 6 (June 1985) - Fitzgerald, M
Abstract : A consecutive series of 95 3 to 4 year old and 43 7 to 11 year old children attending surgical, and medical outpatient clinics was studied, using questionnaires that measured behavioural deviance and had adequate reliability and validity for screening populations of children. A control group was also studied in the 7 to 11 year old sample. Depressive symptoms in the mothers of the children were determined using the Wakefield depression inventory. There was considerable behavioural deviance in children attending the outpatient clinics; 44% of the 7 to 11 year olds who were surgical outpatients had deviant scores. Thirty two per cent of mothers of medical outpatients had deviant scores on the depression inventory. These findings have relevance for the approach paediatricians take to their outpatients.